Damage Analysis In SMP (S Mode Processing) And Installation Of RMM (Radar Maintenance Monitoring) Radar MSSR Mode S - Muhammad Caesar Akbar; Steve Imanuel Lubis (LPPM Universitas PGRI Sumatera Barat, 2024)
As the technology grows rapidly, the aviation keep developing in its servent. On Perum LPPNPI Palembang, equipped with Flight Surveillance Facility MSSR Mode S Radar which works to detect the airplane position arounds by sending the interrogation pulse to gain distance information, velocity, altitude, and airplane identity after the transponder sending the reply pulse. The S Mode Processing (SMP) and the Radar Maintenance Monitoring (RMM) is used by the radar to process the reply pulse form the transponder. This study focuses on the alarm SMP indicator in the RCMS and the PC monitor data radar viewer which not operating. This study was designed with analysis method and checking method. The data was gained from the analysis of voltage value on each part of the PC. Problem solving conducted suitable with the valid SOP on Perum LPPNPI Palembang. The study result is replacing the battered motherboard on SMP PCU and reconfigurating the motherboard to operate as RMM PCU suitable with the procedure on Manual Book Radar MSSR Mode S Eldis.